Development of an algorithm to detect and reduce complexity of drug treatment and its technical realisation - Wurmbach, Viktoria; Schmidt, Steffen J.; Lampert, Anette; Frick, Eduard; Metzner, Michael; Bernard, Simone; Thürmann, Petra A.; Wilm, Stefan; Mortsiefer, Achim; Altiner, Attila; Sparenberg, Lisa; Szecsenyi, Joachim; et al. (BMC medical informatics and decision making, 2020)
The increasing complexity of current drug therapies jeopardizes patient adherence. While individual needs to simplify a medication regimen vary from patient to patient, a straightforward approach to integrate the patients’ perspective into decision making for complexity reduction is still lacking. We therefore aimed to develop an electronic, algorithm-based tool that analyses complexity of drug treatment and supports the assessment and consideration of patient preferences and needs regarding the reduction of complexity of drug treatment.
Gesehen am 23.10.2020